Vegetal fibers in polymeric composites: a review - Fernandes Pereira, Paulo Henrique (2015)
The need to develop and commercialize materials containing vegetal fibers has grown in order to reduce environmental impact and reach sustainability. Large amounts of lignocellulosic materials are generated around the world from several human activities. The lignocellulosic materials are composed of cellulose, hemicellulose, lignin, extractives and ashes. Recently these constituents have been used in different applications; in particular, cellulose has been the subject of numerous works on the development of composite materials reinforced with natural fibers. Many studies have led to composite materials reinforced with fibers to improve the mechanical, physical, and thermal properties. Furthermore, lignocellulosic materials have been treated to apply in innovative solutions for efficient and sustainable systems. This paper aims to review the lignocellulosic fibers characteristics, as well as to present their applications as reinforcement in composites of different polymeric matrices.